Penatalaksanaan Fisioterapi pada Carpal Tunnel Syndrome Dextra dengan Ultrasound dan Nerve Gliding Exercise - Annas Figar Syahya; Boki Jaleha (Inovasi Kesehatan Global, 2024)
Carpal tunnel syndrome (CTS) is a disease of the wrist caused by repetitive movements in an abnormal position continuously and for a long time, so that the median nerve in the wrist becomes pinched or compressed. Risk factors that may influence the event CTS include age, gender, and occupational factors. The problem experienced by the patient is pain in the wrist, tingling in the palms that spreads to the fingers. Therefore the provision of interventions using ultrasound aims to reduce pain, andexercise therapy aims to increase the range of motion of the joints, increase muscle strength, and restore functional activity.